Phylogeny, divergence time estimation, and biogeography of the genus Heterobasidion (Basidiomycota, Russulales) - Chen, Jia-Jia; Cui, Bao-Kai; Zhou, Li-Wei; Korhonen, Kari; Dai, Yu-Cheng (Fungal Diversity Press, 2015)
There have been several investigations into the genus Heterobasidion, however, differentiation of species in these studies have depended on the gene regions analyzed. Reliable defining of species, establishing species divergence times and establishing species biogeographical distributions have been challenging. Here, we used a multilocus phylogenetic approach and maximum parsimony, maximum likehood, and Bayesian analyses to infer the phylogenetic relationships of Heterobasidion species. In addition, we focused on a fungus fossil-based approach and used the largest subunit of RNA polymerase II-the second subunit of RNA polymerase II (RPB1-RPB2) dataset to perform maximum likelihood-based estimation and Bayesian binary analyses, to assess the divergence and biogeographical distributions of Heterobasidion species. The Heterobasidion annousum/ H. insulare species complex clusters in three groups in the phylogenetic analyses. Molecular dating suggests that ancestral Heterobasidion species originated in Eurasia during the Early Miocene, followed by dispersal and speciation to other continents during the Middle Miocene and Early Pliocene. Our data are compatible with the previous viewpoint that H. irregulare and H. occidentale colonized North America via different routes, which has been interpreted as Beringian and Thulean North Atlantic vicariance. In addition, we propose that the occurrence of H. araucariae in the southern Hemisphere was probably due to recent human-mediated introductions. Plate tectonics and long-distance dispersal are the most likely factors that influenced Heterobasidion speciation and biogeography.
Keywords: biogeography; divergence time; Heterobasidion; phylogeny; refugia